Exposure to traffic and lung function in adults: a general population cohort study. Issue 6 (24th June 2015) - Carlsen, Hanne Krage; Modig, Lars; Levinsson, Anna; Kim, Jeong-Lim; Toren, Kjell; Nyberg, Fredrik; Olin, Anna-Carin
Abstract : Objectives: To investigate the association between living near dense traffic and lung function in a cohort of adults from a single urban region. Design: Cross-sectional results from a cohort study. Setting: The adult-onset asthma and exhaled nitric oxide (ADONIX) cohort, sampled during 2001–2008 in Gothenburg, Sweden. Exposure was expressed as the distance from participants' residential address to the nearest road with dense traffic (>10 000 vehicles per day) or very dense traffic (>30 000 vehicles per day). The exposure categories were: low (>500 m; reference), medium (75–500 m) or high (<75 m). Participants: The source population was a population-based cohort of adults (n=6153). The study population included 5441 participants of European descent with good quality spirometry and information about all outcomes and covariates. Outcome measures: Forced vital capacity (FVC) and forced expiratory volume in 1 s (FEV1 ) were measured at a clinical examination. The association with exposure was examined using linear regression adjusting for age, gender, body mass index, smoking status and education in all participants and stratified by sex, smoking status and respiratory health status. Results: We identified a significant dose–response trend between exposure category and FEV1 (p=0.03) and borderline significant trend for FVC (p=0.06) after adjusting for covariates. High exposure was associated with lower FEV1 (−1.0%, 95% CI −2.5% to 0.5%) and lower FVC (−0.9%, 95% CI −2.2% to 0.4%). The effect appeared to be stronger in women. In highly exposed individuals with current asthma or chronic obstructive pulmonary disease, FVC was lower (−4.5%, 95% CI −8.8% to −0.1%). Conclusions: High traffic exposure at the residential address was associated with lower than predicted FEV1 and FVC lung function compared with living further away in a large general population cohort. There were particular effects on women and individuals with obstructive disease.